2014
DOI: 10.1002/ange.201309691
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Wavelength Fluorescent Reporters for Monitoring Protein Kinase Activity

Abstract: In vivo optical imaging must contend with the limitations imposed by the optical window of tissue (600-1000 nm). Although a wide array of fluorophores are available that are visualized in the red and near-IR region of the spectrum, with the exception of proteases, there are few long wavelength probes for enzymes. This situation poses a particular challenge for studying the intracellular biochemistry of erythrocytes, the high hemoglobin content of which optically obscures subcellular monitoring at wavelengths l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…[32,119b] The sensors based on quenchers quenching the fluorescence through electrostatic interactions after phosphorylation, can also be microinjected into cells to detect the activity of PKA. [86] Morris and coworkers used a designed peptide (CPP named pep-1 [120] ) to help chemosensors travel into the cellular cytoplasm. [121] Pep-1 and the chemosensor form noncovalent interactions, and the chemosensor based on protein assistance can internalize into the cells.…”
Section: Sensors In Cellulomentioning
confidence: 99%
See 2 more Smart Citations
“…[32,119b] The sensors based on quenchers quenching the fluorescence through electrostatic interactions after phosphorylation, can also be microinjected into cells to detect the activity of PKA. [86] Morris and coworkers used a designed peptide (CPP named pep-1 [120] ) to help chemosensors travel into the cellular cytoplasm. [121] Pep-1 and the chemosensor form noncovalent interactions, and the chemosensor based on protein assistance can internalize into the cells.…”
Section: Sensors In Cellulomentioning
confidence: 99%
“…Lawrence and coworkers suggested that negatively charged quenching groups could be screened to interact with peptides through electrostatic interactions. When the peptide is phosphorylated by the kinase, the negative charge of the phosphate group interacts with the positive charge of the peptide, thereby forcing the quencher group away from the peptide [86] (Figure 6B).…”
Section: Sensors In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…Activatable probes are characterized by high sensitivity and specificity, which are superior to ''always on'' probes because the switch from the ''off'' to ''on'' state upon interaction with a specific enzyme at the target site allows signal amplification to detect enzyme activity in real time. However, the majority of the currently reported enzyme-activatable probes are only responsive to the hydrolase family (e.g., protease [52,55], kinase [56]). The design of new activatable imaging probes for the detection of other classes of enzymes remains a challenge.…”
Section: Summary and Perspectivesmentioning
confidence: 99%